Unveiling the project fAcilitating Public & Private secuRity operAtors to mitigate terrorIsm Scenarios against soft targEts – APPRAISE: the future for preventing and providing security for soft targets - Morgado, Sónia M.A.; Nabais, Tiago; Felgueiras, Sérgio Ricardo Costa Chagas (ISCPSI/ICPOL, 2024)
Since the dawn of time, the path of humanity has been followed by the need for security in numerous fields. Globalisation as an apparently irreversible process (Morgado, 2013a) incarcerates constant challenges and changes that influence strategic decisions (Morgado & Felgueiras, 2021), whether in law enforcement agencies (LEAs), security policies or counter-terrorism approaches. Regardless of “the dynamics of the geo-strategic, geo-political, geo-territorial, and geo-criminal contexts”, security “is a vital public good and a fundamental and foundational right of life in society.” (Morgado & Felgueiras, 2022, p. 57).
Keywords: Polícia; Ciências Policiais; ISCPSI; Ensino Superior Policial